THE PROBLEM OF FORMING THE SPIRITUAL-MORAL VALUES OF STUDENTS IN THE CONDITIONS OF THE EDUCATIONAL ENVIRONMENT - Palamar, Svetlana (Educological discourse, 2017)
Particular attention requires not only competence but also the willingness to become a socially mature person. It should be noted that along with universal values, we can observe pseudo-values, which are formed in a short period of time, which considerably worsen the behavior of young people. The author highlights the main problems of contemporary youth and reveals the ways of forming spiritual and moral values of students in the educational environment of a higher pedagogical educational institution. The article focuses on the problem of the formation of spiritual and moral values of students in the educational environment.